2021
DOI: 10.1038/s41467-021-24444-7
|View full text |Cite
|
Sign up to set email alerts
|

Lactate sensing mechanisms in arterial chemoreceptor cells

Abstract: Classically considered a by-product of anaerobic metabolism, lactate is now viewed as a fundamental fuel for oxidative phosphorylation in mitochondria, and preferred over glucose by many tissues. Lactate is also a signaling molecule of increasing medical relevance. Lactate levels in the blood can increase in both normal and pathophysiological conditions (e.g., hypoxia, physical exercise, or sepsis), however the manner by which these changes are sensed and induce adaptive responses is unknown. Here we show that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 74 publications
2
48
0
Order By: Relevance
“…The carotid bodies (CB's) glomus cells (type I) have long been known as the body's main O 2 sensors (Ortega-Sáenz and López-Barneo, 2020). In light of recent evidence, however, they are now appreciated for their ability to "sense and respond" to a variety of non-respiratory stimuli including angiotensin II, leptin, cytokines, insulin, and lactate (Conde et al, 2014(Conde et al, , 2020Torres-Torrelo et al, 2021). Their strategic location at the bifurcation of the common carotid arteries allows them to act as multimodal chemosensors and thus play multiple roles in homeostasis beyond respiratory control.…”
Section: Introductionmentioning
confidence: 99%
“…The carotid bodies (CB's) glomus cells (type I) have long been known as the body's main O 2 sensors (Ortega-Sáenz and López-Barneo, 2020). In light of recent evidence, however, they are now appreciated for their ability to "sense and respond" to a variety of non-respiratory stimuli including angiotensin II, leptin, cytokines, insulin, and lactate (Conde et al, 2014(Conde et al, , 2020Torres-Torrelo et al, 2021). Their strategic location at the bifurcation of the common carotid arteries allows them to act as multimodal chemosensors and thus play multiple roles in homeostasis beyond respiratory control.…”
Section: Introductionmentioning
confidence: 99%
“…In support of this idea, it has been reported that rates of glucose uptake in the CB are enhanced during hypoxia ( Obeso et al, 1993 ). Indeed, multiple groups have observed that lactate can also directly stimulate the CB in a concentration dependent manner, with a threshold of approximately 5–10 mM and maximum response achieved at around 30 mM ( Chang et al, 2015 ; Peng et al, 2020 ; Torres-Torrelo et al, 2021 ). Arterial blood lactate concentrations can rise to approximately 6–7 mM during exposure to hypoxia (10% inspired) in mice and it is debatable whether this would be sufficient to excite the CB ( Chang et al, 2015 ; Torres-Torrelo et al, 2021 ).…”
Section: Is An Elevation In Lactate and Stimulation Of Olfactory Rece...mentioning
confidence: 99%
“…Due to relatively stable arterial partial pressures of oxygen and carbon dioxide during incremental exercise ( Sun et al, 2001 ; Forster et al, 2012 ), acute activation of PChRs is debatable in this context. On the other hand, it could be hypothesized that the rising on-exercise concentration of other (than oxygen and carbon dioxide) known CBs stimulants, such as lactate ( Torres-Torrelo et al, 2021 ), potassium ( McLoughlin et al, 1995 ), adenosine ( McQueen and Ribeiro, 1981 ), and catecholamines ( Lahiri et al, 1981 ), could contribute to excessive ventilation due to hyperreflexia of PChRs in HF. According to that notion, not only “tonic” but also “acute” reactivity of CBs would be involved in ExIn in HF patients ( Scott et al, 2003 ).…”
Section: Determinants Of Exertional Dyspnoea In Heart Failurementioning
confidence: 99%
“…In those studies, PChR were blocked with the use of oxygen or opioids, which resulted in improved exercise capacity of HF subjects. Whether such benefit was related to a decrease in acute reflex response to the metabolites of exercising muscles (e.g., lactate) ( Torres-Torrelo et al, 2021 ) or to the dimished tonic activity of PChRs remains unknown.…”
Section: Introductionmentioning
confidence: 99%